Innovationen bei Betonbrücken. Issue 2 (28th January 2021) - Haveresch, Karlheinz
Abstract: Neue Anforderungen beim Ersatzneubau von Brücken haben starke Innovationen bei der Gestaltung, Bemessung und Bautechnik von Betonbrücken ausgelöst. Es ergeben sich sehr interessante neue Lösungsmöglichkeiten. Im Beitrag wird über den Bearbeitungsstand dieser Entwicklungen berichtet, insbesondere für den erweiterten Einsatz von Fertigteilen aus Beton, die Verwendung von Hochleistungsbeton, die Rahmenbedingungen für Spannglieder in Stegen von Überbauten mit Kastenquerschnitt und für Quervorspannung von Fahrbahnplatten sowie für die Bemessungsregeln bei Dekompressionsnachweis und Mindestbewehrung für beschleunigtes Bauen. Abstract: Innovations in concrete bridges New requirements, when it comes to bridge reconstruction, lead to significant innovations concerning design, calculation and construction technology of concrete bridges. Consequently, interesting solution possibilities arise. Therefore, this paper refers to the progress of these solution possibilities, specifically to the extended use of precast concrete members, the use of high‐strength concrete and the definition of determining factors for the use of tendons within webs of superstructures with box cross section as well as transversal tendons within slabs. Moreover, design rules for the decompression limit of prestressed concrete bridges and the minimum reinforcement for an acceleration of construction process are pointed out.